The Role of the Tjong a Fie Museum in Preserving Chinese Cultural Heritage in Medan - Mutiara Febriani Haluet; Fadlul Rahman (AMK : Abdi Masyarakat UIKA, 2026)
The Tjong A Fie Mansion Museum is one of the most significant Chinese cultural heritage sites in Medan, representing historical narratives, cultural values, and the long-standing process of acculturation since the colonial era. This study aims to analyze the role of the Tjong A Fie Museum in preserving Chinese cultural heritage and to examine how the museum functions as a medium for education, tourism, and cultural identity reinforcement. The research employs a literature review method by examining books, scholarly articles, policy documents, and institutional publications relevant to cultural heritage preservation and Chinese-Indonesian history. The collected data were analyzed using a descriptive qualitative approach. The findings reveal that the museum holds strong historical and architectural value through its combination of Chinese, European, and Malay design elements, as well as its authentic collections that illustrate the socio-economic life of the Chinese community in early 20th-century Medan. The museum plays crucial roles in conservation, education, and socio-cultural representation through the preservation of artifacts, educational programs, and cultural activities that support Medan’s multicultural identity. Additionally, the museum serves as a key attraction in the development of heritage tourism, contributing to sustainable cultural tourism and historical awareness. However, several challenges persist, including limited conservation funding, low engagement among younger generations, and modernization pressures in the Kesawan area. This study emphasizes the need for cross-sector collaboration, digital preservation, area revitalization, and strengthened educational initiatives to ensure the sustainability of the museum as a center for Chinese cultural heritage. Thus, the Tjong A Fie Museum serves not only as a repository of historical objects but also as a symbol of acculturation, tolerance, and the historical identity of the city of Medan.